Impacts of Perceived Environmental Variability on Patterns of Work Related Communication - Tushman, Michael L. (Academy of Management Journal, 1979)
This study investigates the impact of environmental variability on communications within and outside a large R extra-unit communication was inversely related to perceived environmental variability, suggesting that communication with external areas may be mediated by special boundary roles.